A reflection of preservice teachers on e-portfolio assessment - Genc, Zulfu; Tinmaz, Hasan (Elsevier Science Bv, 2010)
E-portfolio assessment is getting more important as online teaching and learning activities are disseminating into instructional processes. Preservice teachers, as the current students and prospective teachers, must possess enough level of skills, abilities, and knowledge on e-portfolio development stages including their preparation, development and evaluation. Therefore, this study aims to gather the ideas of preservice teachers (n = 42) from Computer Education and Instructional Technology department who are quite familiar with different technologies. Before and after they actually develop their own e-portfolios, preservice teachers asked several open-ended questions about e-portfolios. Pre and post assessment were analyzed with qualitative data analysis. Results showed that preservice teachers perceive e-portfolios as a context for publishing their work (assignments, projects, and etc.) especially yielded from project based courses. Preservice teachers are divided into three groups with respect to the focus of e-portfolio assessment; only product oriented, only process oriented and both process and product oriented decision making. In subsequent to their e-portfolio development, the process of creating e-portfolios has been reshaped in students' minds from content-to-context to context-to-content. Preservice teachers noted that evaluation of an e-portfolio should mostly concentrate on its visual design, its embedded content and its usability. Although students reported that their skills and abilities extended with e-portfolio development, preparation of e-portfolio websites was defined as the challenge. (C) 2010 Published by Elsevier Ltd.
1st World Conference on Learning, Teaching and Administration (WCLTA) -- OCT 29-31, 2010 -- Amer Univ, Cairo, EGYPT
Keywords: Alternative assessment; e-portfolio; learning and teaching process